Guidelines on advance defences to hostile take-overs - Murphy, A J A (Centre for Law and Society, 2024)
Take-overs A take-over involves a change of control of a company.1 This occurs when the , existing shareholders of a target (or offeree) company transfer sufficient shares to an offeror so as to give to the offeror control of the voting power attaching to the target company's share cap~tal.2 This will occur - (a) where the offeror acquires all or over 50% of the voting shares in the target company; or (b) depending on the nature of the shareholding structure of the target company, effective de facto control may be achieved with less than a 50% shareholding in the target company. Shareholders in many large companies do not bother to vote in person or by proxy at general meetings of shareholders so that a 30% shareholding may give de facto control over a target company.3